Украјинска агенција у јапанском дискурсу: Све у реду са Владом и Људима, док је академија у невољи - Hosaka, Sanshiro (Journal of Regional Security, 2023)
Russia’s full-scale invasion of Ukraine has highlighted the problems of the Japanese academic discourse on Ukraine. This essay has two purposes. First, it describes how Russia’s invasion has altered Tokyo’s official policies and public discourse by driving away Russian disinformation and propaganda narratives while articulating the multiple chasms among academics regarding Ukraine and Russia. Second, it highlights the embedded assumptions commonly seen in many researchers dealing with post-Soviet space: Russia-centered ontology (e.g., “Ukraine is a periphery of Russia”, “fraternal nations”) and anti-hegemonic epistemology that blames the collective West for “Russophobia.”